EFFICACY AND SAFETY OF CURCUMA LONGA EXTRACT IN THE TREATMENT OF OSTEOARTHRITIS: A SYSTEMATIC REVIEW - FAHIRA, ALESSA; SORAYA, ALLYSA; ACHMADSYAH, ARMAND; HAKIM, RANI WARDANI (International Journal of Applied Pharmaceutics, 2019)
Objective: Osteoarthritis (OA) is a chronic disease caused by inflammation of the tissue and bony structure of the joint, which affects more than 235 million people worldwide. Due to the adverse effects caused by the long-term use of standard treatment of OA, the attempt to find natural remedies to treat chronic diseases continues to rise. Curcuma longa is known to have anti-inflammatory effects, which may impact the pathophysiology of OA. While many randomized controlled trials show the efficacy of Curcuma longa extract in the treatment of OA, there has been no comprehensive review of this evidence. Methods: We systematically searched PubMed, Cochrane, Scopus, ProQuest, EBSCOhost, and ScienceDirect for randomized controlled trials that evaluated Curcuma longa extract (CE extract) vs. control (placebo or other therapy). Three trials were identified. Data were then extracted from the studies and summarized descriptively. Results: Across all trials, Curcuma longa therapy was proven to reduce Visual Analog Scale (VAS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores significantly compared to the control group. Adverse effects were less likely to appear in patients treated with Curcuma longa extract compared to other groups. Conclusion: CL extract is beneficial as an alternative medication for OA treatment, shown by the reduced scores of the Visual Analog Scale (VAS) and WOMAC in all studies we reviewed.